PENGARUH MODEL PEMBELAJARAN INDEX CARD MATCH (ICM) TERHADAP KETERAMPILAN MENGANALISIS TEKS NARASI SISWA KELAS V SD - Maria Sesilia Koi Wukak Matarau; Amelia Widya Hanindita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The background of this research is that students can be actively engaged in learning activities when using the Index Card Match (ICM) model. ICM encourages students to review the learning materials presented during the learning activities, while also training them to develop a more thorough understanding of the skills required to analyze the lesson content. The purpose of this research is to examine the effects of ICM on the ability to analyze narrative texts by fifth-grade students. The study employed an experimental design with a pre-test and post-test group, which includes two categories: the control group and the experimental group. The descriptive test, which consisted of a pre-test and post-test, was the data collection technique used in this research. Data analysis, including normality tests, homogeneity tests, and hypothesis testing, was performed using SPSS 21. The analysis of the hypothesis test revealed a significant result with a two-tailed test value of 0.000, which is smaller than 0.05, indicating a significant difference in variation before and after the treatment. Therefore, it can be concluded that the ICM method had an effect on the ability to analyze narrative texts among fifth-grade students at SDN Tenggilis Mejoyo 1 Surabaya.